Предмет: Математика,
автор: alenamazonenko
выражение 7-2х и 9х-8(х+1) принимают равные значения
Ответы
Автор ответа:
0
7-2х= 9х-8(х+1)
7-2х = 9х - 8х-8
7-2х = х-8
-2х-х = -8-7
-3х = -15
х = 5
При х = 5 выражения принимают равные значения
7-2х = 9х - 8х-8
7-2х = х-8
-2х-х = -8-7
-3х = -15
х = 5
При х = 5 выражения принимают равные значения
Похожие вопросы
Предмет: Химия,
автор: gaara1922
Предмет: Алгебра,
автор: jdhskskdkdksidj
Предмет: Английский язык,
автор: Аноним
Предмет: Физика,
автор: marlll
Предмет: Физика,
автор: mirasovadiana